Penerapan Metode Taguchi Untuk Meningkatkan Produktifitas pada Produksi LPG di PT.CVX - nana sugiono (Lembaga Penelitian Universitas Balikpapan, 2018)
Abstract— One of the factors for maintaining existence of the product is keep the quality of products .The quality of products gas ( propane ) can be measured with the results of the percentage propane recovery and levels propane which passes to residue gas .Factor that influences quality control gas ( propane is the temperature at refrigerant system , speed refrigerant compressor , recycle valve opening of , the temperature at hot oil system , temperature tower , pressure tower and the flow of bait in every tower and one factor unrestrained the weather . Combination the level of factors on initial conditions used is a1b1c1d1e1f1g1 which are ( temperature refrigerant system at the temperature -27 & speed refrigerant compressor at 90 % speed, recycle valve opening of with temperature -27 & temperature hot oil system at the temperature 215 & temperature tower at the temperature 138 & pressure tower to pressure 200 psig and the flow of bait every tower in 1250 bbld with rerata propane recovery namely 90,56 % and levels propane which passes to residue gas namely 0,274 Taguchi method used to increase performance products .Based on a method of taguchi produced combination the level of a factor that is either by rerata the percentage propane recovery namely 91,04 % and rerata propane levels which passes to residue gas namely 0,263 % .Combination the level of factors that elected is a1b1c2d1e1f1g1 which are ( temperature refrigerant system at the temperature -27 f , speed refrigerant compressor at 90 % speed , recycle valve opening of with temperature -25 f , temperature hot oil system at the temperature 215 f , temperature tower at the temperature 138 f , pressure tower to pressure 200 psig and the flow of bait in every tower in 1250 bbld